2018
DOI: 10.1080/00313831.2017.1420685
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Children’s Social Functioning and Reading Proficiency: A Systematic Review of the Quality of Educational Assessment Instruments Used in Norwegian Elementary Schools

Abstract: Social functioning and reading proficiency are critical for success in school and society. Therefore, identifying children with such problems is important. This study had 2 parts: first, a random sample of 234 elementary schools was surveyed about which instruments they use to assess reading proficiency and social functioning. Second, a systematic review of the quality of these instruments was conducted using international standards for examining the quality of assessment instruments. The survey showed that sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…The participants in this study expressed uncertainty about this, because they did not have sufficient knowledge if the assessment instruments and work methods used had any scientific basis and/or proven experience. Similar conclusions were drawn by Arnesen et al (2019) when exploring the quality and use of educational assessment instruments in schools in Norway. They concluded that the assessment instrument had weak or undocumented qualities and new more efficient assessment instruments were needed that supported the teachers work to a greater extent.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The participants in this study expressed uncertainty about this, because they did not have sufficient knowledge if the assessment instruments and work methods used had any scientific basis and/or proven experience. Similar conclusions were drawn by Arnesen et al (2019) when exploring the quality and use of educational assessment instruments in schools in Norway. They concluded that the assessment instrument had weak or undocumented qualities and new more efficient assessment instruments were needed that supported the teachers work to a greater extent.…”
Section: Discussionsupporting
confidence: 74%
“…More knowledge is needed about the quality and use of educational assessment instruments in Swedish preschools. In Norway, educational assessments for social functioning and reading proficiency were explored (Arnesen, Braeken, Ogden, & Melby-Lervåg, 2019). They concluded that the instruments used in schools had, in some aspects, weak or undocumented qualities; therefore, they proposed the need of more differentiated assessment instruments in school to facilitate the teachers' work.…”
Section: Educational Language Observation and Assessmentsmentioning
confidence: 99%
“…Although individuals with dyslexia had been previously diagnosed with dyslexia by psychological or pedagogical professionals, a linguistic test, Language 6-16 (Ottem & Frost, 2011) were used to confirm group affiliation. Language 6-16 has good reliability and validity as reported in a recent review (Arnesen, Braeken, Ogden, & Melby-Lervåg, 2018). Adults with dyslexia were included if the summarized score from Language 6-16 were below 1 standard deviation (SD) of the mean.…”
Section: Participantsmentioning
confidence: 99%
“…Mooij, 2000;Mooij and Smeets, 2009). Still, to our knowledge, little tradition for the systematic use of educational assessment instruments that can lead to effective instructions for social skills to promote students' success in school (Arnesen, Braeken, Ogden, and Melby-Lervåg, 2017). For instance, in Norway, there are only a few validated instruments available for use in schools (e.g.…”
Section: Social Skills Related To School Successmentioning
confidence: 99%
“…Teachers most often rely on their own judgements without systematic descriptions, which can be haphazard and unreliable (Arnesen et al, 2017). Although most teachers have sufficient experiences to judge students' social functioning and classroom behaviour informally on a regular basis, these judgements might be inconsistent or inaccurate.…”
Section: Social Skills Related To School Successmentioning
confidence: 99%